Evaluation of vertical seismic response for a large scale beam supported aqueduct. - Li, Yuchun (Earthquake engineering & structural dynamics.)
By the theories of potential flow and structural vibration, the formulae for evaluating the 'wet' (with water) frequencies and mode shapes of the beam supported aqueduct are derived through a simplified fluid structure interaction analysis. The time history formulae of structural responses to the vertical seismic excitation are obtained. Applying the response spectrum principle, the equivalent vertical earthquake load exerted on the beam and the corresponding effects are also derived. Several illustrative examples are conducted. The analytical results show that : (i) The 'wet' frequencies of the structure are lower than the corresponding 'dry' (without water) frequencies due to the participating water mass, but the 'wet' mode shapes are identical to the corresponding 'dry' ones. (ii) The water mass plays an important role in the vertical seismic response, which varies with the different geological sites. For the different seismic inputs, the deeper the water is, the greater are the structural responses. (iii) The vertical seismic effects on the beam are generally not too small to be neglected and should be considered in the structural designsof a beam supported aqueduct.